2017
DOI: 10.1093/ecco-jcc/jjx089
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of 6-Thioguanine Nucleotide Levels and Clinical Remission in Inflammatory Bowel Disease

Abstract: This study reinforces the link between 6-thioguanine nucleotide levels and clinical remission in inflammatory bowel diseases, also exploring the validity of specific 6-thioguanine nucleotide thresholds to predict clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…15 The adverse genotoxic effects of thiopurine therapy are largely caused by the latter pharmacodynamic effect. The 6-TGN levels are positively correlated with efficacy in patients with IBD, 16 so in the case of inefficacy or loss of response an attempt should be made to increase the 6-TGN level. The dosage can be increased, or in case of a skewed metabolism (a preferential generation of methylated metabolites, measured as 6-methylmercaptopurine ) at the cost of 6-TGN) other drugs that beneficially influence metabolism can be coadministered, such as allopurinol.…”
mentioning
confidence: 99%
“…15 The adverse genotoxic effects of thiopurine therapy are largely caused by the latter pharmacodynamic effect. The 6-TGN levels are positively correlated with efficacy in patients with IBD, 16 so in the case of inefficacy or loss of response an attempt should be made to increase the 6-TGN level. The dosage can be increased, or in case of a skewed metabolism (a preferential generation of methylated metabolites, measured as 6-methylmercaptopurine ) at the cost of 6-TGN) other drugs that beneficially influence metabolism can be coadministered, such as allopurinol.…”
mentioning
confidence: 99%
“…Yet, in what is perhaps the most comprehensive meta-analysis of 6-TGN levels and remission in IBD, Estevinho et al (58) systematically reviewed all published evidence of thiopurine use in IBD up to 2017. After screening over 1,000 studies identified by searching four online databases, 25 studies were ultimately deemed eligible for analysis of 6-TGN mean value and cut off levels.…”
Section: Thiopurine Metabolitesmentioning
confidence: 99%
“…Most of the clinical trial literature with AZA and 6MP is based on trials that used weight-based dosing. 2 Although there is a rationale for using therapeutic drug monitoring (TDM)-based dosing, there is very limited clinical trial data to show that TDMbased dosing is safe and effective. 3 6TG has been used in patients with allergies to AZA or 6MP but has an increased risk of veno-occlusive disease and nodular regenerative hyperplasia, 4 and allopurinol has been used to reduce shunting of 6MP to 6MMP in nonresponders to AZA/6MP who develop transaminitis.…”
Section: Pharmacologymentioning
confidence: 99%